Analisa SWOT Strategi Digitalisasi pada Era New Normal untuk Pertumbuhan Ekonomi di Sumatera, Indonesia - Ranila Suciati; Kery Utami; Belardo Prasetya Mega Jaya (Jurnal Ilmiah Aset, 2021)
The spread of COVID-19 has almost never been predicted by any part of the world. This affects most business fields in terms of global supply, world demand, and the confidence of economic actors. The spread of COVID-19 has caused several business activities which become the driving force of the economy stopped due to government policies. The stay at home policy disrupts the performance of the business field, most of which conduct physical buying and selling transactions. And it has directly impact to a negative economic growth both globally and in every region of Indonesia, including Sumatra including 10 provinces within. For this reason, a SWOT analysis is needed to determine the best strategies that can drive economic growth. This analysis based on logics to enhance Strength and Opportunities, nevertheless at the same time could minimize weakness and overcoming Threats. The results of the position of the Cartesian diagram in this study were to diversify products / technologies both e-commerce and fintech and to carry out the results of the SWOT matrix strategy. After analyzing the SWOT matrix, the results in this study were to choose the S-T strategy, namely using strength to overcome threats.